Dampak Bank Keliling di Kampung Cikeyeup Desa Gunung Anten - Hasanah, Siti Badriyatul; Fadilah, Safira Qireina; Khasanah, Jaojatul; Meysaroh, Siti (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This article aims to find out about the behavior of mobile bank borrowers and consider what problems the presence of these banks causes for the local community. This mobile bank is very popular among the lower middle class because it provides easy loan services and a fast process. This convenience makes mobile banks popular and accepted by the public as "emergency fund providers". Therefore, this article contains an explanation of how people behave in kp. Cikeyeup, especially for cash borrowers at mobile banks and what are the reasons behind mothers taking out loans at mobile banks. This research uses a qualitative method with a descriptive approach. Data was collected using interview techniques and direct observation at the research location. The results of the research carried out showed that many people were affected by this mobile bank. Many problems arise, ranging from the family's economy or finances becoming increasingly suffocated, damage to family relationships, to damage to social relations between neighbors. This happens because many people take loans from more than one bank and use the names of other people who have never taken loans from that bank. So many people end up trapped by the practice of digging holes to pay off debts.